2017
DOI: 10.1111/jofo.12188
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling for allopatricStrix(Strigiformes: Strigidae) owls in South America: determinants of their distributions and ecological niche-based processes

Abstract: Strix (Strigidae) is a worldwide genus of 17 owl species typical of forested habitats, including Rusty‐barred Owls (S. hylophila), Chaco Owls (S. chacoensis), and Rufous‐legged Owls (S. rufipes) in South America. These species are distributed allopatrically, but the ecological traits that determine their distributions remain largely unknown and their phylogenetic relationships are unclear. We used species distribution models (SDMs) to identify variables explaining their distribution patterns and test hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Hypothesized rates of taxon adaptation in novel environments were proposed by Peterson, Soberón, and Sánchez‐Cordero () to be slower than the process of extinction, thereby largely restricting daughter species to ancestral environmental niches. Many subsequent studies have found evidence to instead support the incidence of niche divergence, focusing on taxa including lizards (Losos et al., ), pheasants (Wang et al., ), and owls (Girini, Palacio, & Zelaya, ). Environmental niche models of arid‐adapted taxa have not been studied in depth, the exception being lizards and frogs (Catullo, Lanfear, Doughty, & Keogh, ; Edwards, Keogh, & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesized rates of taxon adaptation in novel environments were proposed by Peterson, Soberón, and Sánchez‐Cordero () to be slower than the process of extinction, thereby largely restricting daughter species to ancestral environmental niches. Many subsequent studies have found evidence to instead support the incidence of niche divergence, focusing on taxa including lizards (Losos et al., ), pheasants (Wang et al., ), and owls (Girini, Palacio, & Zelaya, ). Environmental niche models of arid‐adapted taxa have not been studied in depth, the exception being lizards and frogs (Catullo, Lanfear, Doughty, & Keogh, ; Edwards, Keogh, & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…2). To reduce collinearity among variables, a correlation matrix was computed based on 1000 points drawn randomly from each accessible area, and a subset of less correlated variables was selected (Pearson's correlations < |0.8|; Girini et al 2017). Nine climatic (annual mean temperature range, mean diurnal range, maximum temperature of warmest month, temperature annual range, mean temperature of wettest quarter, annual precipitation, precipitation of driest month, precipitation of wettest quarter and precipitation of warmest quarter) and ten climatic variables (annual mean temperature range, mean diurnal range, isothermality, maximum temperature of warmest month, temperature annual range, mean temperature of wettest quarter, mean temperature of driest quarter, mean temperature of warmest quarter, annual precipitation and precipitation of wettest month) were selected for eryngos and straight-billed reedhaunter distributions, respectively.…”
Section: Distribution Modelingmentioning
confidence: 99%
“…Rather than being a drawback, though, this may represent an opportunity for SDMs to shed light on ecological knowledge on rare and cryptic birds. Indeed, SDMs have shown high performance for identifying important environmental variables explaining the distributions of birds with these characteristics (Gibson et al 2007, Tinoco et al 2009, Marini et al 2010, Botero-Delgadillo et al 2012, Wu et al 2012, Girini et al 2017. In this context, and given that birds are one of the most well-known taxonomic groups, avian SDMs provide a suitable model into which include biotic interactions (Engler et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations should test the host–parasite interaction. For instance, an examination of Strix rufipes —the only Strix species reported in Chile [ 40 ], and which predates A. olivacea [ 41 ]—for the presence of Sarcocystis sp. P61 could unveil a definitive host for this putative new taxon of the Sarcocystidae family.…”
Section: Discussionmentioning
confidence: 99%